Peripheral synucleinopathy in Parkinson disease with LRRK2 G2385R variants. Issue 3 (1st February 2021) - Yang, Jing; Wang, Hao; Yuan, Yanpeng; Fan, Shiheng; Li, Lanjun; Jiang, Chenyang; Mao, Chengyuan; Shi, Changhe; Xu, Yuming
Abstract: Objective: Recent studies demonstrated cutaneous phosphorylated α synuclein (p‐syn) deposition in idiopathic and some monogenetic Parkinson disease (PD) patients, suggesting synucleinopathy identical to that in the brain. Although the LRRK2 Gly2385Arg (G2385R) variant is a common PD risk factor in the Chinese population, the pathogenesis of PD with G2385R variant has not been reported. We investigated whether synucleinopathy and small fiber neuropathy (SFN) are associated with the G2385R variant. Methods: We performed genotyping in 59 PD patients and 30 healthy controls from the skin biopsy database. The scale of SFN was assessed, as well as bright‐field immunohistochemistry against antiprotein gene product 9.5 (PGP9.5) and double‐labeling immunofluorescence with anti‐PGP9.5 and anti‐p‐syn. Results: (1) p‐syn deposited in the skin nerve fibers of G2385R carrier PD patients, which was a different pattern from noncarriers, without no difference observed between proximal and distal regions; (2) decreased distal intraepidermal nerve fiber density was found in both the G2385R carrier and the noncarrier PD group, and was negatively correlated with composite autonomic symptom score‐31 item (COMPASS‐31) scores; (3) PD patients with the G2385R variant showed a more peculiar clinical profile than noncarriers with a higher nonmotor symptoms scale, COMPASS‐31 score, and levodopa equivalent dose, in addition to an increased prevalence of certain autonomic symptoms or rapid eye movement sleep behavior disorders. Interpretation: Synucleinopathy is related to the LRRK2 G2385R genotype and implies a different pathogenesis in G2385R variant carriers and noncarriers. This study also extended the clinical profiles of PD patients with the G2385R variant.